Forwarding credible information in multi-agent systems - Krümpelmann, Patrick (2009)
In this work we extend the communication abilities of agents in multi-agent systems by enabling them to reason about the credibility of information to be shared with other agents. We propose a framework in which agents exchange sentences of a logical language enriched by meta-information. We discuss several possible approaches and present an advanced approach overcoming previously shown problems. For this, we make use of a calculation method for the plausibility of information known from approaches to belief dynamics in multi-agent systems. Moreover, we present how this can be implemented in a multi-agent system. © 2009 Springer-Verlag Berlin Heidelberg.